Federated States of Micronesia Public Expenditure Analysis : Getting Ready for 2024 - World Bank (World Bank, Washington, DC, 2017)
The Federated States of Micronesia (FSM) has a very narrow production base, with subsistence agriculture and fisheries and the public sectors dominating the economy, both with regard to employment and value added. The contribution of institutional sectors to growth suggests that private enterprises relied on the public sector for growth opportunities and households tended to fall back to subsistence when growth slows. Growth accelerations and decelerations were largely influenced by the implementation of the U.S. funded airport upgrade project and Compact grants although over the long run, the net effect of public investment on growth has been small. Economic growth and international competitiveness are severely constrained by the country’s small size, remoteness, geographic isolation and dispersion, and thin institutional and human capacity. This Public Expenditure Review (PER) is aimed at filling a knowledge gap to support the Government of FSM (GoFSM) in improving the design of public expenditure policies to address these key challenges. The main recommendations of this PER to support the GoFSM in addressing the aforementioned challenges are centered on how to (a) improve public expenditure management to support macroeconomic stability and growth, and (b) improve public expenditure management to support efficient, effective, and equitable service delivery. The PER is composed of a concise set of chapters analyzing macroeconomic and fiscal trends, intergovernmental relationships, public investment management (PIM) issues, and the two largest expenditure sectors: education and health. Data limitations may result in some inaccuracies and inadvertent distortions in outcomes.